“Text” interaction in EFL virtual classroom during the COVID-19 era: Actual use and sense of virtual community - Amekhlafy, Sultan Saleh Ahmed; Alqahtani, Abdullah Ayidh J. (Frontiers in Education, 2022)
The era of the Covid-19 compelled universities to design and deliver courses online. However, the successful design and delivery of online courses should embrace community. This study correlates the actual use of text interaction in EFL virtual classes (VC) and its impact on the sense of virtual community (SOVC). To achieve the study's goal, three groups of Preparatory Year (PY) students at Najran University studying online through Blackboard in the era of Covid-19 represent the participants. The study used data sources of the analysis of 9 archival data of reading course, Listening and Speaking course and Writing course VC using Schullo (2005) model and the SOVC questionnaire adopted from (Koh & Kim 2003) as well as an individual interview of nine instructors to get thorough interpretations of text interaction during VC. The study provided detailed information about what type(s) of text interaction participants used in English as a Foreign Language (EFL) virtual classrooms. It also explored the impact of VC text interaction on EFL students’ SOVC. The study found that text interaction in EFL VC enhanced students’ SOVC. The findings supported that text interactions had both academic and social values. The study contributed to the theory of SOVC and brought recommendations on how educators can take advantage of VC text interaction in the EFL context.